RISE: The data is talking to you. Are you listening? / Nur Syazwani Ahamad Azahari - Ahamad Azahari, Nur Syazwani (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
Imagine you have a problem to solve. Based on readings and observations, a solution for the problem can be suggested. However, assumptions without testing, observations without information, data without analysis and decisions without proof will only cause questions and fail to convert this critical data analysis process to information and knowledge.